2019
DOI: 10.12659/msm.913289
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of Hemodynamic Changes in Patients After Off-Pump Coronary Artery Bypass Graft Surgery Using Impedance Cardiography

Abstract: Background This study aimed to investigate the role of impedance cardiography (ICG) to evaluate hemodynamic changes in patients after off-pump coronary artery bypass graft (OPCABG) surgery. Material/Methods One-hundred and sixty patients who had undergone OPCAGB were enrolled and assessed using New York Heart Association NYHA functional class (II, II, and IV). ICG was used to measure the stroke volume (SV), stroke volume index (SI), cardiac output per minute (CO/min), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…ICG uses the thoracic electrical impedance to assess hemodynamics and possesses good prospects in clinical application. A study showed that after coronary artery bypass graft, the EF, SV, CO, and CI monitored by ICG were correlated with the results obtained by echocardiography ( 26 ). TFC is an indicator of ICG that reflects the amount of fluid in the chest cavity, which could reflect the cardiac preload by recording the changes in fluid impedance.…”
Section: Discussionmentioning
confidence: 91%
“…ICG uses the thoracic electrical impedance to assess hemodynamics and possesses good prospects in clinical application. A study showed that after coronary artery bypass graft, the EF, SV, CO, and CI monitored by ICG were correlated with the results obtained by echocardiography ( 26 ). TFC is an indicator of ICG that reflects the amount of fluid in the chest cavity, which could reflect the cardiac preload by recording the changes in fluid impedance.…”
Section: Discussionmentioning
confidence: 91%
“…In this single-center study changes were analyzed in the hemodynamic profile of AMI patients by using ICG. Although a good correlation between impedance diagnostics and invasive assessment of cardiac output and systemic vascular resistance has been reported [10,11], thus far, data is mostly limited to heart failure [12][13][14][15][16][17][18][19] and with only a few AMI subsets examined [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…In patients after off-pump coronary artery bypass grafting, the findings obtained from ICG were correlated with B-type natriuretic peptide (BNP) levels and TTE measurements for the evaluation of cardiac hemodynamic changes during perioperative period [10].…”
Section: Introductionmentioning
confidence: 99%
“…The ICG is a non-invasive diagnostic tool enabling reliable assessment of patients' hemodynamic profile [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%